PENGARUH PENGGUNAAN UMPAN BALIK (FEEDBACK) TERHADAP HASIL BELAJAR SISWA DALAM MATA PELAJARAN FIQIH - Tomi Apra Santosa; Wulan Sari; Abi Suar; Jalwis Jalwis (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2020)
The purpose of the study was to find out the effect of user feedback on students' learning outcomes in fiqh subjects. This research includes quasi-experiments. The data is obtained through tests. Data analysis techniques Test t. Before implementing the hypothesis, a prerequisite test is carried out. The results showed that students without using the technique of feedback averaged 72.86 students with a standard deviation of 6,712 and variance of 45,055 and the value of students who used feedback techniques obtained from Postest grades with an average score of 82.50 with a standard deviation of 7,532 and variance of 56,751. The hypotheses obtained by T hitung = 3,838 > Ttabel = 2,145, the influence of the use of feedback on students' learning outcomes in the eyes of fiqh learning in grade XI IPA MAN 3 Kerinci. Learning with feedback techniques is suitable to be applied in public and religious schools.